1997
DOI: 10.1103/physrevb.56.13464
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy studies of theTiO2(110)surface: Structure and the nucleation growth of Pd

Abstract: The surface structure of TiO 2 ͑110͒ has been reexamined using scanning tunneling microscopy ͑STM͒, especially in terms of its temperature dependency. A dramatic topographic change was observed around 725 K, which is most likely due to the oxygen desorption into the gas phase and the simultaneous diffusion of Ti into the bulk. The atomically resolved STM images show a strong dependency on the tip composition and allow a double-bridging oxygen vacancy to be identified. The nucleation and growth of Pd on the TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(132 citation statements)
references
References 37 publications
12
118
2
Order By: Relevance
“…[2,[8][9][10]. Nevertheless, the present EXAFS results reject the hypothesis of the five-fold Ti adsorption site for Ni.…”
Section: Methodscontrasting
confidence: 41%
See 1 more Smart Citation
“…[2,[8][9][10]. Nevertheless, the present EXAFS results reject the hypothesis of the five-fold Ti adsorption site for Ni.…”
Section: Methodscontrasting
confidence: 41%
“…Most of those studies have indicated that the metal interacts mainly with oxygen, especially bridging oxygen atoms [3][4][5][6]. On the other hand, experiments on metal clusters and TiO2(110) such as XPS and STM have suggested that the metal preferably interacted with the five-fold Ti sites [7][8][9][10]. This contradiction might arise from the lack of direct information related to the bond between the single metal atom and the TiO2 surface.…”
Section: Introductionmentioning
confidence: 92%
“…70 A metal-to-insulator transition is observed as the size of Au nanoparticles decreases below 3 nm by measuring the tunneling current as a function of the bias voltage (I -V) 2 and by measuring the local barrier height (LBH). 69 This behavior has also been observed for Pd/TiO 2 -(110), 25 for Ag particles grown in nanopits on a graphite surface, 71 and for Ag particles supported on Al 2 O 3 /NiAl-(110). 72 The valence band structures of (1 × 1) monolayer and (1 × 3) bilayer Au films on reduced titania are significantly different from those of bulk Au, 58 for example, the electronic properties of the ordered Au films being quite different compared with bulk gold.…”
mentioning
confidence: 58%
“…34 the adsorption energy, particle shape, and the electronic structure of deposited Au nanoparticles and to influence their unique catalytic properties. 2,9,14,17,19,[25][26][27][28][29][30][31][32] Theoretical calculations have demonstrated that Au particles bind more strongly to a defect-rich surface compared with a defect-deficient surface and that significant charge transfer occurs from the titania support to the Au particles. 2,9,30,31 High-resolution STM combined with density functional theoretical (DFT) calculations 31 has confirmed that bridging oxygen vacancies are the active nucleation sites for Au particles on titania and that each vacancy site can bind approximately three Au atoms on average.…”
Section: Surface Defects and Sinter-resistant Supportsmentioning
confidence: 99%
“…The preferential growth at the step edges has been observed in the growth of metals on periodic substrates in a number of systems. Palladium growth on the oxide substrates serves as such an example [23][24].…”
Section: Higher Coveragesmentioning
confidence: 99%